Naomi and Ely$1 (Bs no kiss list s - Cohn, Rachel; Levithan, David (New York : Alfred A. Knopf, 2007)
Although they have been friends and neighbors all their lives, straight Naomi and gay Ely find their relationship severely strained during their freshman year at New York University.
Keywords: Interpersonal relations -- Fiction; Homosexuality -- Fiction; Dating (Social customs) -- Fiction; New York (N.Y.) -- Fiction